Analisis Waktu Proses Bongkar Muat Barang dengan Menggunakan Teori Antrian - Renatha Hutapea (Universitas Bunda Mulia, 2017)
The analysis of queuing time has done for the process of loading and unloading as well as clarify why the biggest cause of problems occurred in the queue (45% of the total issues arising for the service) on company which is engaged in the business of providing warehouse.Currently, the queue model used is Multichannel Single Phase models where there are 10 lines for the loading process, assisted by 12 people for forklifts and 2 people to the process of checking in and out of the goods with the time standards set by the company is 30 minutes. Sample data retrieval is done by measuring the customer arrival and service time that occurred for three days. Data processing is done with using OM EXCEL software to calculate the amount of time in the queue. From the measurement results obtained that the average customer arrival (truck) is 3 trucks/hour so that the average service for a truck 13 minutes. And from the results obtained by processing server utilization 6% and 54% probability of unemployment system. Customer waiting time is much less than 30 minutes. The percentage of total issues in the company does not fully describe the queue at organization. This is due to the queue remains occur only upon arrival at a particular customer accumulates.